Kyphectomy and sliding growing rod technique in patients with congenital lumbar kyphosis deformity with myelomeningocele - Karataş, Muhammed Enes; Bayram, Yusuf; Şafak, Halid; Kar, İlyas; Sağlam, Necdet; Uçar, Bekir Yavuz (BioMed Central Ltd, 2024)
Objective Neural tube defects are the most common congenital disorders after cardiac anomalies. Lumbar kyphosis deformity is observed in 8-15% of these patients. This deformity severely limits the daily lives of these patients. In our study, we aimed to correct the kyphosis angle of the patients with lumbar kyphosis associated with myelomeningocele (MMC) and allow them to continue their growth without limiting their lung capacity by applying kyphectomy and sliding growing rod technique. Patients and methods In this study, we retrospectively evaluated 24 patients with congenital lumbar kyphosis deformity associated with MMC, aged between 4 and 9 years, and who applied to Umraniye Training and Research Hospital between the dates of 2018 and 2021. We evaluated preoperative and postoperative kyphosis angles, correction rates, bleeding during operations, operation time, level of instrumentation, number of the resected vertebrae, initial levels of the posterior defects, duration of hospital stays, annual lengthening, and weight of the patients. Results Mean age was 5.04 (between 4 and 9). Mean preoperative and early postoperative kyphosis angles were 129.8 degrees (87-175 degrees) and 0.79 degrees (- 20-24 degrees), respectively. The kyphotic deformity correction rate was 99.1%. A difference was found regarding kyphosis measurements between preoperative and early period values (p < 0.05). The annual height lengthening of patients was calculated as 0.74 cm/year and 0.77 cm/year between T1-T12 and T1-S1, respectively. Mean preoperative level of hemoglobin (Hgb) was 11.95, postoperative Hgb value was 10.02, and the decrease was significant (p < 0.05). In terms of complications, 50% (12) had broken/loosen screws, 50% (12) had undergone debridement surgery, 37.5% (9) had vacuum-assisted closure therapy, and 33.3% (8) had to get all of their implants removed. Conclusion We believe that our sliding growing rod technique is a new and updated surgical method that can be applied in these patient groups, facilitating the life, rehabilitation process, and daily care of MMC patients with lumbar kyphosis. This technique seems to be a safe and reliable method which preserves lung capacity and allows lengthening.
Keywords: Spina Bifda; Myelomeningocele; Kyphosis; Kyphectomy; Spine; Sliding Growing Rod